YsxC, an essential protein in Staphylococcus aureus crucial for ribosome assembly/stability - Cooper, Elizabeth L (BioMed Central, 2009)
BACKGROUND: Bacterial growth and division requires a core set of essential proteins, several of which are still of unknown function. They are also attractive targets for the development of new antibiotics. YsxC is a member of a family of GTPases highly conserved across eubacteria with a possible ribosome associated function. RESULTS: Here, we demonstrate by the creation of a conditional lethal mutant that ysxC is apparently essential for growth in S. aureus. To begin to elucidate YsxC function, a translational fusion of YsxC to the CBP-ProteinA tag in the staphylococcal chromosome was made, enabling Tandem Affinity Purification (TAP) of YsxC-interacting partners. These included the ribosomal proteins S2, S10 and L17, as well as the (β)' subunit of the RNA polymerase. YsxC was then shown to copurify with ribosomes as an accessory protein specifically localizing to the 50 S subunit. YsxC depletion led to a decrease in the presence of mature ribosomes, indicating a role in ribosome assembly and/or stability in S. aureus. CONCLUSIONS: In this study we demonstrate that YsxC of S. aureus localizes to the ribosomes, is crucial for ribosomal stability and is apparently essential for the life of S. aureus.